Aerial morphometry in Moringa oleifera Lam. at different planting densities, in savannahs of Monagas, Venezuela: Agroindustria - Granado Gimón, Raul (2025)
In order to evaluate the primary morphometric variables, of branches and leaves per plant, in moringa, an experiment was set up at the “Guachimarí” farm, Maturín municipality, Monagas state, Venezuela. A nursery was created to produce seedlings, which were later transplanted to the field. A randomized block design was used, with five treatments or planting densities (16,000; 20,000; 26,666; 40,000 and 80,000 plants.ha-1), four repetitions and experimental units of 9 m2. The harvest was carried out 215 days after transplantation. Prior to this, the primary aerial morphometry was determined: plant height (PH), basal stem diameter, number of branches and the robustness index RI); after this, the branch morphometric variables were quantified: length, diameter, number of leaves and height to the first branch (HFB); and in the leaf: length and width. The values were studied using the ANOVA procedure, descriptive statistics, regression analysis and correlations. Planting density did not affect (P>0.05) most of the foliage morphometric variables, except for RI and HFB, with coinciding maxima, close to the critical density of 50,000 plants·ha-1, and influenced by physical limitations of the soil. In morphometric correlations, the variable PH was positively associated with variables measured in branch and leaf (r= 0.71**); in contrast, there was a negative association between the number of branches·plant-1 and the number of leaves·branch-1 (r= -0.74**). Genetic and physiological aspects of the crop are involved, especially the habit of vertical growth at high rates.